2022
DOI: 10.1039/d2ra01306a
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites of Livistona decipiens as potential inhibitors of SARS-CoV-2

Abstract: Promising natural inhibitors for COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Other plant crude extract that have been evaluated against cathepsin L includes Carica papaya , Averrhoa carambola , Ageratum conyzoides (Hariono et al, 2021), Ginkgo biloba leaves extract (Xiong, Zhu, Zhang, et al, 2021), Camellia sinensis crude extract, Theobroma cacao crude extract, Dark chocolate crude extract (Zhu & Xie, 2020), Shuanghuanglian (Su et al, 2020), Turmeric rhizomes, mustard seeds and wall rocket extracts (Guijarro‐Real et al, 2021), Tea ( Camellia sinensis ) (Upadhyay et al, 2020), Haritaki (Terminalia chebula) (Upadhyay et al, 2020), Aqueous Extracts from Taraxacum officinale Leaf (Tran et al, 2021), Reynoutria sachalinensis (Nawrot‐Hadzik et al, 2021), Ephedra sinica ethanol extracts (Mei et al, 2021), Scutellaria baicalensis 70% ethanol extract (Liu, Gao, et al, 2021), Scutellaria barbata D. Don aqueous extracts (Huang et al, 2021), Averrhoa carambola leaves and Ageratum conyzoides aerial part methanolic extracts (Hariono et al, 2021), Lophophora decipiens leaves and fruit extracts (El‐Hawary et al, 2022) exhibited inhibitions towards SARS‐CoV‐2 3CL pro . Scutellaria barbata D. Don aqueous extracts (Huang et al, 2021) exhibited inhibitory effects on SARS‐CoV‐2 3CL pro and TMPRSS2 activity.…”
Section: Plants and Natural Products Anti‐sars‐cov‐2mentioning
confidence: 99%
“…Other plant crude extract that have been evaluated against cathepsin L includes Carica papaya , Averrhoa carambola , Ageratum conyzoides (Hariono et al, 2021), Ginkgo biloba leaves extract (Xiong, Zhu, Zhang, et al, 2021), Camellia sinensis crude extract, Theobroma cacao crude extract, Dark chocolate crude extract (Zhu & Xie, 2020), Shuanghuanglian (Su et al, 2020), Turmeric rhizomes, mustard seeds and wall rocket extracts (Guijarro‐Real et al, 2021), Tea ( Camellia sinensis ) (Upadhyay et al, 2020), Haritaki (Terminalia chebula) (Upadhyay et al, 2020), Aqueous Extracts from Taraxacum officinale Leaf (Tran et al, 2021), Reynoutria sachalinensis (Nawrot‐Hadzik et al, 2021), Ephedra sinica ethanol extracts (Mei et al, 2021), Scutellaria baicalensis 70% ethanol extract (Liu, Gao, et al, 2021), Scutellaria barbata D. Don aqueous extracts (Huang et al, 2021), Averrhoa carambola leaves and Ageratum conyzoides aerial part methanolic extracts (Hariono et al, 2021), Lophophora decipiens leaves and fruit extracts (El‐Hawary et al, 2022) exhibited inhibitions towards SARS‐CoV‐2 3CL pro . Scutellaria barbata D. Don aqueous extracts (Huang et al, 2021) exhibited inhibitory effects on SARS‐CoV‐2 3CL pro and TMPRSS2 activity.…”
Section: Plants and Natural Products Anti‐sars‐cov‐2mentioning
confidence: 99%
“… 19 A recent report on the leaves and fruit extracts of the plant also showed inhibitory activity against coronavirus. 20 The fruits of L. chinensis are edible in eastern Asia, they are a component of prepared soups used in the treatment of liver cancer and chronic hepatitis. 21 The nutritional evaluation of the leaves and fruits of L. australis also showed that the fruits are a good source of calcium and potassium.…”
Section: Introductionmentioning
confidence: 99%